Adrenergic Manipulation Inhibits Pavlovian Conditioned Approach Behaviors - Pasquariello, Kyle Z. (Behav Brain Res, 2017)
Environmental rewards and Pavlovian reward cues can acquire incentive salience, thereby eliciting incentive motivational states and instigate reward-seeking. In rats, the incentive salience of food cues can be measured during a Pavlovian conditioned approach paradigm, in which rats engage in cue-directed approach (“sign-tracking”) or approach the food delivery location (“goal-tracking”). While it has been shown that dopamine signaling is necessary for sign-tracking, some studies [e.g. 1] have suggested that norepinephrine is involved in learning to sign-track as well. Thus, in order to investigate the influence of norepinephrine in Pavlovian conditioned approach, we administered three adrenergic drugs while rats learned that a food cue (an illuminated, retractable lever) preceded the delivery of banana-flavored food pellets into a food-cup. We found that pre-session injections of disulfiram (a dopamine-β-hydroxylase inhibitor) inhibited the development of sign-tracking, but goal-tracking was only affected at the high dose. In one experiment, post-session injections of disulfiram blocked the development of sign-tracking, although this effect was not replicated in a separate set of rats. Post-session injections of prazosin (an α1-adrenergic receptor antagonist) and propranolol (a β-adrenergic receptor antagonist) also blocked the development of sign-tracking but not goal-tracking. Taken together, these results suggest that adrenergic transmission mediates the acquisition of sign-tracking but not goal-tracking, and thus plays a selective role in the attribution of incentive salience food cues.